Second Graders’ Grapho-Motor Skill Learning and Verbal Learning: The Effects of Socio-Educational Factors - Hollander, Chagit; Adi-Japha, Esther (Frontiers in Psychology, 2021)
Introduction: Children from low socio-economic status (SES) families, and in particular, those with a lower level of maternal education, show lower vocabulary scores and lower fine-motor skills than their SES peers whose mothers have a higher level of education. Furthermore, low SES children frequently have difficulties in reading and spelling. These difficulties are attributed to deficits in the intentional acquisition of knowledge, such as those required in verbal learning, alongside deficits in the acquisition of knowledge through practice, such as those required for developing visual-motor routines. The aim of the current study was to test the effect of two background factors: risk of reading and spelling difficulties and low maternal education (ME) on practice-dependent learning motor tasks and in second graders from low SES families. Methods: In 2016/17, 134 low-SES second graders with higher and lower ME (95 typical learners and 39 with reading and spelling difficulties) were assessed with (a) the Invented Letter Task (ILT; a grapho-motor skill learning task) across five time-points (initial- and end-training Day 1; initial- and end-training Day 2; and two-weeks post-training) and an ILT transfer task; and (b) The Rey Auditory Verbal Learning Test (RAVLT; an intentional word-learning task in which a word list is read to children for five learning trials and is recalled 20 minutes later). Findings: Lower ME was associated with surplus segments in the performance of the motor task and its transfer to a novel condition as well as with lower recall on the verbal task, but not with the learning of both the motor and the verbal task. Having reading and spelling difficulties affected motor-task accuracy and also the way children learned the task, as evidenced by surplus segments at the beginning of Day 2, which were reduced with further practice. Conclusions: Low ME affects performance level in low SES children, while reading and spelling difficulties results in an atypical learning curve. Future research on practice-dependent learning in the context of children coming from low SES families should focus on subgroups within this heterogeneous population.